A study to assess the clinicopathological spectrum of acute complications of diabetes mellitus type II - Lala, Kunal; Bhati, Viren; Lala, Divya; Patil, Smita (International Journal of Research in Medical Sciences, 2020)
Background: The acute metabolic complications of diabetes consist of diabetic ketoacidosis (DKA), hyperosmolar non-ketotic coma (HNC), lactic acidosis (LA), and hypoglycemia. All of these are associated with significant morbidity and mortality. These can easily be prevented by early recognition and prompt management. Therefore, this study was conducted to assess the clinicopathological spectrum of acute complications of diabetes mellitus type II. Methods: This observational, analytical study was conducted on 100 patients aged more than 18 years admitted in the ICU with acute complication of Diabetes mellitus Type II. Medical history was recorded. Physical examination and investigations were done and recorded. Results: The mean age of the study population was 55.26±13.13 years. Hypoglycemia was more common (63%) than DKA (37%). Fever and sweating had the overall highest incidence (and were more in patients with hypoglycemia) while stupor, nausea and abdominal pain had the lowest incidence (and were more in patients with DKA). On examination, only one patient of DKA was drowsy. Mean temperature, pulse and respiratory rate were higher in the patients having DKA while blood pressure was higher in patients having hypoglycemia. Conclusions: It can be effectively concluded from the present study that DKA and hypoglycaemia have a broad spectrum of clinicopathological features. But the incidences vary widely. This may help in early recognition of the impending complication and thereby enabling prompt management of the same, reducing the associated morbidity and mortality.